Initiating a Room‐Temperature Rechargeable Aqueous Fluoride‐Ion Battery with Long Lifespan through a Rational Buffering Phase Design. Issue 14 (19th February 2021) - Li, Xuejin; Tang, Yongchao; Zhu, Jiaxiong; Lv, Haiming; Xu, Yan; Wang, Wenlong; Zhi, Chunyi; Li, Hongfei
Abstract: Previously reported fluoride‐ion batteries (FIBs) can only work at high temperatures (>150 °C) with solid electrolytes or organic electrolytes. Aqueous FIB has barely been reported due to the unstable F – electrochemistry in aqueous electrolytes. In addition, the electrode materials commonly suffer from serious and adverse volume expansion during the conversion reaction. Herein, a stable aqueous F – electrochemistry is realized by a rational buffering phase design in which stagger distribution of BiF3 and Bi7 F11 O5 phases is achieved. The enhanced F – electrochemistry is systematically studied and suggests that the Bi7 F11 O5 phase plays a vital role in the stability and reversibility of the electrode due to its lower volume change and higher electronic conductivity. Pulverization and dissolution of active species issues are also suppressed. As a result, the assembled battery delivers excellent cycling stability, high reversibility, and superior rate capability, which is far better than conventional solid fluoride shuttle batteries. Mechanism studies demonstrate that the capacity comes from reversible conversion between Bi 3+ and Bi 0 with an intermediate phase of Bi7 F11 O5 . This work initiates room‐temperature FIBs with aqueous electrolytes and provides a good cycling lifespan, which pave the way to a more practical fluoride ion storage system. Abstract : A room‐temperature, rechargeable, aqueous fluoride‐ion battery is demonstrated with the assistance of K + electrochemistry. A rational buffering phase design strategy is developed to address the instability of the electrode in an aqueous electrolyte. Benefiting from this design, the as‐assembled batteries deliver a high capacity and good cycling stability, which are far better than conventional solid fluoride shuttle batteries.